Penetration of cefixime into fibrin clots and in vivo efficacy against Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. - Bergeron, M G (1986)
The experimental model of infected fibrin clots in rabbits was used to study the penetration and in vivo activity of cefixime against Klebsiella pneumoniae, Escherichia coli, and Staphylococcus aureus. The respective MICs of cefixime against these strains were 0.25, 2, and 8 micrograms/ml. The clots were infected with 10(6) to 10(8) CFU/g. Groups of four animals for each strain received an intravenous injection of 100 mg of cefixime per kg over 30 min. High peak levels were observed in serum (146.5 micrograms/ml) and clots (15.8 micrograms/g), and the antibiotic was still detectable in the clots (0.6 micrograms/g) 24 h after administration. The respective serum and clot elimination half-lives were 0.7 and 5.0 h. The mean serum protein binding was 23.8 +/- 3.8%. Cefixime was highly bactericidal against K. pneumoniae and E. coli and reduced, over a 24-h period, their respective colony counts by 7.8 log10 and 6.2 log10 CFU/g of fibrin. It was less effective against S. aureus but still reduced the bacterial counts by 2.8 log10 CFU/g of fibrin. The present results demonstrate that cefixime, a new broad-spectrum oral cephalosporin, has a long tissue half-life which ensured, at the dose given here, good in vivo bactericidal activity against both gram-positive and gram-negative bacteria up to 24 h after administration of the antibiotic.